Effect of neck muscles vibration on postural balance and spatial frame of reference: A systematic scoping review - Jamal, K.; Leplaideur, S.; Chochina, L.; Moulinet Raillon, A.; Bonan, I. (Annals of physical and rehabilitation medicine, 2018)
Muscle vibration, in particular applied to the neck muscle is increasingly being used as a mean of rehabilitation treatment. Neck muscle vibration (NMV) is thought to have an effect on the representation of the body in space through sensory recalibration. The objective of this systematic scoping review was to map out the characteristics of the existing studies and gather the effect of neck muscle vibration on both spatial frame of reference and on postural balance. following the PRISMA guidelines, a systematic search was carried out using the databases MEDLINE, EMBASE, Cochrane library and PEDrO applying the following key words [(Postural balance) OR (Spatial reference)] AND (Neck muscle vibration) for those articles published through to July 2016. Altogether 67 studies were assessed and they unveiled both a large heterogeneity and a standard quality of methodology with a total of 1522 participants included. Under unilateral neck muscle vibration, the visual environment (illusion of a visual target) seemed to move towards the opposite side of the vibration, and both the visual vertical and the straight ahead were shifted towards the vibrated side. In addition, NMV produce a body tilt. This effect is however not constant at all times. NMV is considered as a useful remedy tool in rehabilitation therapy which has shown to induce a body sway on the force platform and a deviation of the spatial representation in both healthy subjects and patients. That said, however, owing to the heterogeneity of the experiences and the various significant shortfalls highlighted, this research does not allow us to firmly conclude our results.